Analysis Of Macrofauna, and Fruit Body Populations of Ectomycorrhizal Fungi in Shorea leprosula Standing: Analisis Populasi Makrofauna, Mesofauna, dan Tubuh Buah Fungi Ektomikoriza Pada Tegakan Shorea leprosula - Mesi Arisinta; Risma Maghfiroh; Eni Nuraeni (BiosciED: Journal of Biological Science and Education, 2026)
The populations of macrofauna, mesofauna, and fruiting bodies of ectomycorrhizal fungi in Shorea leprosula stands in the Gunung Dahu Research Forest (HPGD) provide important insights into the relationship between forest restoration and edaphic community dynamics. This study reviews the results of this research by comparing findings from ten supporting journals that discuss aspects of soil ecology, soil fauna biodiversity, and ectomycorrhizal associations in tropical ecosystems. Based on the review results, the main study shows that the number and types of soil fauna increase along with the growth of from restoration, where 13 types of macrofauna and mesofauna and 10 types of ectomycorrhizal fruiting bodies dominated by the genus Russula were found. This review emphasizes that the success of ecosystem restoration is not only measured by vegetation growth, but also by the recovery of complex soil biotic functions.